Enhancing relationship marketing: A case study at Binaraya PKINK Sdn. Bhd. / Mohd Hasif Akmal Abd. Halim - Abd. Halim, Mohd Hasif Akmal (2011)
In today's high competitive and globalize business context, increasing customer loyalty emerges as the most important challenges faced by marketers. Educating loyal customers is frequently argued to be the single most important driver of organizations’ long-term performance, which can lead to increased sales and customer share, lower costs, and higher prices. Therefore marketing scholars emphasize the influence of relationship marketing as a strategically important tool from which customer loyalty can be secured and, as a result, the achievement of higher competitiveness and enhanced customer satisfaction can be accomplished. The main focus for this study is to find out the principal issues in enhancing relationship marketing at BINARAYA PKINK SDN.BHD. in order to develop well designed programs to improve relationship marketing by turn new customers into regularly purchasing clients, and then progressively move them through being strong supporters of the company and its product, and finally to being active and vocal advocates for the company thus playing an important role as referral source. The study was carried out on a convenience sample of 200 respondents through the distribution of structured questionnaires to BINARAYA’s existing customers within the area of Pasir Tumboh, Kota Bharu. The data were analyzed using SPSS through the frequencies analysis, correlation coefficient analysis and regression analysis. From the analysis, the researcher found that trust, commitment, communication, and satisfaction have a significant relationship with the relationship marketing. From the findings, it shows that trust is the critical factor while communication is the least important factor. Some conclusions are provided in the research and the researcher also stated several recommendations. It is a great pleasure if BINARAYA’s management is willing to evaluate the suggestions from the respondents and the researcher